DEPICTION OF WOMEN IN RAHI MASOOM RAZA’s ADHA GAON - Jagruti B Bheda (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2020)
Every work of art represents and inheres in topos and chrónos of given milieu and its culture as well as changes occurred in its history. Adha Gaon, where Rahi Masoom Raza portrays the distorting images the Partition, is a fine example for it. Women's considerations, albeit, are a subtext to a narrative that intends to tell its story about half a village in the wake of the Partition. Raza says, "This novel is, in fact, my journey. If I can capture the truth of Garngauli, I will have the courage to write the epic of Gazipur. This novel is really the prologue to that epic. This story is neither religious nor political, because time is neither religious nor political and this story is actually about time. It is the story of time passing through Gangauli." (3)